2021
DOI: 10.5093/pi2021a9
|View full text |Cite
|
Sign up to set email alerts
|

A Personalized Remote Video-Feedback Universal Parenting Program: A Randomized Controlled Trial

Abstract: The randomized controlled trial examined the efficacy of a personalized remote video feedback parenting program to improve parenting and child behavior outcomes. Ninety-two mothers of 2-6-year-old children were randomly allocated into the intervention group (n = 50) and waiting-list control group (n = 42). The Strengthening Bonds preventive program was performed to improve positive parenting. The mothers participated in one in-person group session. During six weeks, the mothers received, via smartphone, remote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 61 publications
0
6
0
3
Order By: Relevance
“…The sample of the present study is a subsample of 60 participants from 92 participants of the RCT study performed in 2019-2020 (Linhares et al, 2022 ). The original sample of the previous RCT study comprised 92 mothers and their children, of which 50 were from the intervention group, and 42 were from the waiting-list control.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The sample of the present study is a subsample of 60 participants from 92 participants of the RCT study performed in 2019-2020 (Linhares et al, 2022 ). The original sample of the previous RCT study comprised 92 mothers and their children, of which 50 were from the intervention group, and 42 were from the waiting-list control.…”
Section: Methodsmentioning
confidence: 99%
“…An innovative parenting program, named Strengthening Bonds, was delivered remotely (via WhatsApp) using a video feedback strategy with customized individual video clips of mothers interacting with their children in play-situation combined with animated video clips (standard examples of positive parenting that explain essential positive dimensions of mother-child interactions) (Linhares et al, 2022 ). A randomized controlled trial using the Strengthening Bonds program showed that the intervention-induced decrease in children’s behavior problems was mediated by a reduction in maternal coercive practices; also, there was a direct effect of the intervention to improve the parental sense of competence (Linhares et al, 2022 ). However, there were no effects of this program on mother-child interaction outcomes, which could be due to the high performance of mothers’ interactive behaviors at the baseline (“ceiling effect”).…”
Section: Introductionmentioning
confidence: 99%
“…O programa Fortalecendo Laços é uma iniciativa inovadora, desenvolvida no contexto do iLab de acordo com a metodologia do IDEAS. Trata-se de um programa de promoção da parentalidade positiva, envolvendo videofeedback personalizado para mães com conteúdos sobre comportamento interativo e práticas positivas maternas e realizado de forma remota via WatsApp (Linhares et al, 2019a;Linhares et al, 2020).…”
Section: O Programa "Fortalecendo Laços" Desenvolvido De Acordo Com O...unclassified
“…O estudo randomizado controlado do Fortalecendo Laços incluiu um grupo controle de lista de espera (waiting list) e as avaliações pré-intervenção e pós-intervenção (Linhares et al, 2022).…”
Section: /12unclassified
See 1 more Smart Citation